Improved evidence-base for Kenya's Agricultural Sector Transformation and Growth Strategy and National Agricultural Investment Plan - CGIAR Research Program on Policies, Institutions, and Markets (2019)
PIM modeling analysis was used to identify priority value chains for targeting public policies and investments in Kenya's Agricultural Sector Transformation and Growth Strategy for 2019-2029 and Kenya's National Agricultural Investment for 2019-2024.